Allograft semilunar cardiac valves processing and cryopreservation - morphology in scanning electron microscope - Krs, O; Burkert, J; Slízová, D; Kobylka, P; Spatenka, J (Cell and tissue banking, 2006)
OBJECTIVE: The most important factors of long term clinical performance of biological heart valve prostheses are methods of processing and cryopreservation. That is why we decided to evaluate the impact of current Allograft Heart Valves (AHV) Bank protocol on valve tissue morphology. Scanning electron microscope (SEM) is a valuable tool for investigation of biological surfaces. In case of cardiac valves it is especially suitable for detection of fine changes in endothelial covering and underlying layers. MATERIAL AND METHODS: "Fresh" aortic and pulmonary AHV samples, harvested from "heart-beating" cadaveric donors, were compared with (1) tissue from AHV obtained from non heart-beating donors, (2) samples stored in 4 degrees C saline for 24 h, (3) antibiotic treated tissue for 24 h at 37 degrees C and finally (4) cryopreserved valves, stored in liquid nitrogen (-196 degrees C) for 6-38 months. All samples were dissected, dried with hexamethyldisilazane (HMDS), gold coated, studied and photographed by SEM (Tesla BS 301). RESULTS: Our alternative method of drying samples by the HMDS method proved to be suitable for thin membranes of human semilunar valves. We were able to detect early changes in the endothelium after harvesting, and denudation of the endothelial covering during preservation with and without freezing. CONCLUSION: SEM (using HMDS drying) along with other methods may be helpful for the morphological control of processing, cryopreservation and liquid nitrogen storage of AHV. According to the current findings we have to avoid washing of AHV in saline after harvesting.
Keywords: srdeční chlopně; Transplantation, Homologous; kryoprezervace; Humans; Microscopy, Electron, Scanning; Cryopreservation; homologní transplantace; lidé; Heart Valves; mikroskopie elektronová rastrovací